LETTUCE GROWN GROWTH IN NUTRIENT SOLUTION WITH DIFFERENT CONCENTRATIONS OF CALCIUM - Ribeiro, A. A.; Simeão, M.; Santos, D. P. (Revista Brasileira de Engenharia de Biossistemas, 2015)
The present study aimed to evaluate the growth of lettuce grown hydroponically with different concentrations of calcium. The experiment was conducted in a greenhouse during the period from November to December 2014 at the Federal University of Piauí - Campus Professor Cinobelina Elvas, located in Bom Jesus, Piauí. The lettuce plants were grown in nutrient solution with increasing concentrations of calcium: 0; 25; 50; 75 and 100% compared to amount recommended for the culture. The experimental design was completely randomized, with five treatments and four replications. The parameters evaluated were: plant height, stem diameter, number of leaves, dry weight of shoot and root and root volume. Up to a level of 25% Ca in nutrient solution there was an increase in plant height, dry weight of leaves and roots. The stem diameter, number of leaves and root volume of lettuce plants were not affected by calcium concentrations present in the nutrient solution.